Improvement of acid soils and rice (Oryza sativa L.) productivity using organic amendments from organic wastes - Maru, Ali (2019)
Rice productivity on tropical soils is very low partly because most of these soils are acidic due to high amounts of Fe and Al which limit rice growth and development, soil nutrients availability, fertilizer use efficiency, and yield. This low rice yield prompted a need to substitute some amount of chemical fertilizers with organic amendments from organic wastes. The general objective was to increase soil physico-chemical properties, rice growth variables, nutrients use efficiency, and rice productivity using organic amendments from organic wastes leucaena leucocephala (tropical and subtropical leguminous plants locally called Petai Belalang), chicken manure, cow dung, forest litter, and chicken litter biochar were co-composted using standard procedures to improve the quality and nutrients content. The study was conducted at Universiti Putra Malaysia Bintulu Campus and transformed wastes were evaluated in a pot study using standard procedures after which potential organic amendments were selected for field and ammonia volatilization studies. The selected treatments were: (i) Soil only (T1), (ii) Existing recommended fertilization (T2), (iii) Biochar-forest litter compost (T3), (iv) Biochar-chicken litter compost (T4), (v) Biochar-cow dung compost (T5), (vi) Biochar-leucaena leucocephala compost (T6), and (vii) Biochar-leucaena leucocephala - chicken litter compost (T7). Three replicates of each treatments in composting, pot study, ammonia volatilization was arranged using Randomized Complete Design. In the field study, four replicates of each treatments arranged using Randomized Complete Block Design were evaluated in first, second, and third planting cycles and thereafter, rice grain quality was determine using dielectric analysis whereas soil physico-chemical properties characterization, soil ammonia loss estimation, plants growth variables, plants nutrients use efficiency, and economic viability of using the soil organic amendments in rice cultivation were determined using standard procedures. Treatments with L. leucocephala showed higher decomposition because of lower C:N ratio over chicken manure, cow dung, and forest litter. Percentage humic acids in forest litter was significantly higher than those of L. leucocephala, chicken manure, and cow dung, however, the functional groups of the humic acids from animal manures were higher than those extracted from plants. Co-application of chicken litter biochar increased the nutrient elements of L. leucocephala, forest litter, chicken manure, and cow dung but reduced compost temperature, composting period, compost humic acids content, and functional groups of the humic acids. Results in pot, ammonia volatilization, and field studies revealed that organic amendments significantly reduced soil acidity especially Fe and Al whereas soil pH, total carbon, and nutrients availability were significantly increased compared soils of the conventional method. The study on ammonia volatilization revealed that ammonia emission from urea was higher with L. leucocephala than those with forest litter, chicken manure, and cow dung. In a field study, the organic amendments improved plant nutrients use efficiency, rice growth variables, and grain yield compared with the existing method of cultivating rice. The co-composted chicken litter biochar improved rice grain yields in the first (9 to 11 t ha-1), second (11 to 13 t ha-1), and third (8 to 10 t ha-1) planting cycles. Inorganic N, P, K, MgO, and trace element fertilizers use were reduced in soils with organic amendments by 25%, 100%, 64%, 100%, and 100%, respectively whereas maturity of rice was also reduced by 20 days over the conventional methods. Although production cost using the new intervention increased by 36.27% over the conventional method in the first and second planting cycles, it reduced by 19.87% in the third planting cycle. Net revenue in the new intervention increased over the conventional method ranging from 248.53% to 662.48% in first, second, and third planting cycles respectively whilst maintaining the quality of rice grains. Among the organic amendments used chicken litter biochar co-composted with L. leucocephala and chicken manure treatment was more profitable for growing MR219 compared with those composted with forest litter, poultry, and cow dung. Hence, it is recommended that small scale rice farmers should be trained on converting their agriculture wastes into organic amendments for detoxifying acidic soils to improve rice productivity.